Implementasi Manajemen Pendidikan Karakter dalam Mengembangkan Minat, Sikap dan Perilaku Positif Siswa di SMAI Integral Hidayatullah Boarding School Batam - Nurharyati, Nurharyati (STAI Denpasar Bali, 2024)
The quality of Indonesian education is the absolute responsibility of the Ministry of National Education which is implemented as a manifestation of macro policies that are applied simultaneously in Indonesia. Policy is a whole set of concepts and principles that become the outline and basis of plans in the implementation of policies set to achieve goals as targets that must be achieved. Problems found by researchers during initial observations of research related to the implementation of character education management at SMAI Integral Hidayatullah Boarding School Batam are Character education management innovations at SMAI Integral Hidayatullah Boarding School Batam have not been fully felt by students as objects of policy implementation. The effectiveness of the implementation of character education management is considered less effective with no synergy found between planning, implementing and evaluating the achievement of character education management targets due to less than optimal school support. This research implements qualitative research methods. Qualitative research activities, the data collected are not numbers but in the form of words or images. The data in question is in the form of interviews, field notes, personal documents and others. The results of the study formulated several efforts made in overcoming obstacles in developing students' interests, attitudes, and positive behaviors at SMAI Integral Hidayatullah Boarding school, one of which is to intensify the discipline of madrasah residents, because discipline is a factor that supports success in improving the quality of education. Strive for learning facilities and infrastructure, utilize free space for religious practice, work on software gradually, and add supporting books through the BOS program, and arouse student interest with various learning methods.